Impact of operations research on improving the logistics efficiency of companies in Benguela - Lusende André , Nanikafuako Augusto (2025)
This research evaluated the impact of Operations Research in the optimization of logistics processes in companies in Benguela (Angola). Using a quantitative approach, representative companies from the logistics sector were selected and surveys and record analysis were applied to characterize their processes and detect areas for improvement. Mathematical models of linear programming, simulation and queuing theory were developed to optimize aspects such as route planning, inventory management and resource allocation, calibrated with real data. The results showed that the implementation of these solutions led to significant improvements in logistics efficiency, including reductions in transportation and storage costs, decreased delivery times, and increased product availability. In addition, opportunities were identified to minimize environmental impact through route optimization and cargo consolidation, thus evidencing Operational Research as a key tool for sustainability in this sector.